Західні риси зображень янголів на кахлях Мазепиної столиці - Мезенцев, В.І. (Сіверщина в історії України, 2024)
Стаття розглядає відомі натепер рідкісні керамічні полив’яні поліхромні та теракотові пічні кахлі з образами янголів-путті доби гетьманування Івана Мазепи (1687–1709 рр.), знайдені під час розкопок у м. Батурині Чернігівської обл. Аналізуються їхні дизайни та декор у широких порівняннях з аналогічними сюжетами на ранньомодерних кахлях, майолікових тарелях, скульптурних рельєфах, малюнках та інших творах образотворчого мистецтва України, Польщі та Італії. Обґрунтовується припущення про запозичення київськими й батуринськими кахлярами мотиву путті з характерними орнаментальними деталями італійського походження від ренесансних і барокових кахлів чи скульптури Речі Посполитої. Показані впливи мистецтва Відродження і бароко Заходу на художню кераміку столиці козацької держави у період найвищого піднесення міста за І. Мазепи. Стаття багато ілюстрована фото й гіпотетичними комп’ютерно-графічними реконструкціями цілих кахлів Батурина, Польщі та горельєфів путті Італії Нового часу. This article closely examines the rare polychrome glazed ceramic and terracotta (unglazed) stove tiles bearing the masterly representations of angels or putti from the reign of Hetman Ivan Mazepa (1687–1709). They have been discovered during the excavations in the town of Baturyn, Chernihiv province, Ukraine, which was the capital of the seventeenth- and eighteenth-century Cossack state, or Hetmanate. The Canada-Ukraine Baturyn Archaeological Project is sponsored by the Canadian Institute of Ukrainian Studies (CIUS) at the University of Alberta and the Ucrainica Research Institute in Toronto, Canada. This project is administered by The Peter Jacyk Centre for Ukrainian Historical Research at the CIUS Toronto Office (https://www.ualberta.ca/canadian-instituteof- ukrainian-studies/centres-and-programs/jacyk-centre/baturyn-project. html). The Ukrainian Studies Fund in New York also supports the Baturyn project with annual subsidies. The most generous individual benefactors of the archaeological and historical investigations of early modern Baturyn are Ms. Olenka Negrych, Dr. George J. Iwanchyshyn (Toronto), and Dr. Maria R. Hrycelak (Park Ridge, IL, USA). The author discusses the designs and adornments of putti on Baturyn’s stove tiles in details and broad comparisons with the analogous motifs on the early modern tiles, table plates, sculptural reliefs, drawings, and other pieces of visual arts in Ukraine, Poland, and Italy. He believes that the tile makers in Baturyn and Kyiv modelled the images of putti with some characteristic ornamental features of Italian origins from the Renaissance and Baroque stove tiles or sculptures of the Polish-Lithuanian Commonwealth. This research provides valuable new insight into the impact of Renaissance and Baroque arts on the decorative ceramics of the Cossack Ukraine capital and its link to European Christian civilization. The article is illustrated with many photos and hypothetical computer graphic reconstructions of three broken early modern Baturyn’s and Polish stove tiles and the Italian sculptures of putti.